The Relationship between Morale and Teacher Performance of SDA Junior High School Teachers in North Sulawesi Province - Sehang, Femmy (11th International Scholars Conference, 2017)
The Objective of research was to study the relationship between, Morale and Teacher performance. The study was conducted at Adventist Junior High School of North Sulawesi Province with 162 Teachers as sample which taken randomly and proportionally in each school by the research method: ex post facto. The study utilized quantitative approach with a questionnaire to collect data. Data were collected by a questionnaire with a Likert -scale which was distributed to respondent of the study. The instrument underwent validity and reliability test before it was used. Correlation and regression analyses were used with the help of software SPSS version 23. Results showed that there was a positive and significant relationship between Morale and Teacher Performance of SDA Junior High School Teachers in North Sulawesi Province. Furthermore, from the results it can then be recommended that Adventist Junior High School Teacher Performance can be improved by enhancing their morale.